Intestinal SEC16B modulates obesity by regulating chylomicron metabolism - Ruicheng Shi; Wei Lu; Ye Tian; Bo Wang (Elsevier, 2023)
Objective: Genome-wide association studies (GWAS) have identified genetic variants in SEC16 homolog B (SEC16B) locus to be associated with obesity and body mass index (BMI) in various populations. SEC16B encodes a scaffold protein located at endoplasmic reticulum (ER) exit sites that is implicated to participate in the trafficking of COPII vesicles in mammalian cells. However, the function of SEC16B in vivo, especially in lipid metabolism, has not been investigated. Methods: We generated Sec16b intestinal knockout (IKO) mice and assessed the impact of its deficiency on high-fat diet (HFD) induced obesity and lipid absorption in both male and female mice. We examined lipid absorption in vivo by acute oil challenge and fasting/HFD refeeding. Biochemical analyses and imaging studies were performed to understand the underlying mechanisms. Results: Our results showed that Sec16b intestinal knockout (IKO) mice, especially female mice, were protected from HFD-induced obesity. Loss of Sec16b in intestine dramatically reduced postprandial serum triglyceride output upon intragastric lipid load or during overnight fasting and HFD refeeding. Further studies showed that intestinal Sec16b deficiency impaired apoB lipidation and chylomicron secretion. Conclusions: Our studies demonstrated that intestinal SEC16B is required for dietary lipid absorption in mice. These results revealed that SEC16B plays important roles in chylomicron metabolism, which may shed light on the association between variants in SEC16B and obesity in human.